Is there a relation between environmental exposure during pregnancy and congenital anomalies in newborn? Preliminary results from a case-control study - Marques, Inês (2018)
BACKGROUND: Maternal exposure to environmental factors has been associated to the birth of a child with specific congenital anomalies (CA). The aiming of this study is to investigate the association between occupational exposure, maternal place of residence, workplace and leisure activities during pregnancy and CA METHODS: In 2016, an observational, case control study was developed and is still in progress. Cases are live births, identified in the maternity unit, with at least one CA and controls are the two births without anomaly following each case. Residents outside the study area, stillbirths and women who decline to participate or are incapable to give consent are excluded RESULTS: Were recruited to the study 116 live births (38 cases and 78 controls). The majority of cases reported living (68.4%) and spend leisure time (63.2%) in the industrial area. 57.7 of controls lives and 46.9% spend leisure time in same area. However no statistical differences were detected between them (p=0.195 for residency and p=0.175 for place of leisure). Cases work more frequently in Lisbon (21%) and residence area (15.8%) compared to controls (17.3% and 15.4% respectively) (p=0.057). A total of 44 CA were detected and the most frequently reported groups was the musculoskeletal system (34.1%) followed by CA of the ear and genital group (15.9% and 15.9 respectively). CONCLUSION: Due to the small sample size, no statistically significant difference was found between cases and controls. Reason why it is necessary to continue the study and obtain the collaboration of other hospitals in the same area.